2016
DOI: 10.15252/embj.201593447
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of yeast V1ATPase in the autoinhibited state

Abstract: Vacuolar ATPases (V-ATPases) are essential proton pumps that acidify the lumen of subcellular organelles in all eukaryotic cells and the extracellular space in some tissues. V-ATPase activity is regulated by a unique mechanism referred to as reversible disassembly, wherein the soluble catalytic sector, V 1 , is released from the membrane and its MgATPase activity silenced. The crystal structure of yeast V 1 presented here shows that activity silencing involves a large conformational change of subunit H, with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
93
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 49 publications
(103 citation statements)
references
References 55 publications
9
93
1
Order By: Relevance
“…A comparison with the recent EM reconstructions of yeast V-ATPase in three states (22) suggests that, upon enzyme dissociation, free V o is halted in state 3. We showed previously that autoinhibited, membrane-detached V 1 -ATPase is halted in state 2 (45), and we propose that this conformational mismatch to state 3 V o could function to prevent unintended reassembly of holo V-ATPase under conditions when the proton pumping activity of the enzyme is not needed.…”
mentioning
confidence: 71%
See 3 more Smart Citations
“…A comparison with the recent EM reconstructions of yeast V-ATPase in three states (22) suggests that, upon enzyme dissociation, free V o is halted in state 3. We showed previously that autoinhibited, membrane-detached V 1 -ATPase is halted in state 2 (45), and we propose that this conformational mismatch to state 3 V o could function to prevent unintended reassembly of holo V-ATPase under conditions when the proton pumping activity of the enzyme is not needed.…”
mentioning
confidence: 71%
“…Recently, we determined the 6.2-to 6.5-Å crystal structure of autoinhibited yeast V 1 -ATPase (40). Interestingly, a comparison of the structure of autoinhibited V 1 with the structure of V 1 as part of holo V-ATPase (22) revealed that the membranedetached V 1 is halted in state 2 based on the rotational position of the DF rotor relative to the inhibitory H subunit (40).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, nucleotide-free V 1 -ATPases seem to form the catalytic dwell state, rather than the ATP-binding dwell and ADP-release dwell states. Recently, the crystal structure of S. cerevisiae V 1 -ATPase has been obtained at a 6.2 Å resolution49. This structure appears to be an inhibitory state wherein the subunit H inhibits the ATPase activity by stabilizing ADP binding to the catalytic site.…”
Section: Discussionmentioning
confidence: 99%